Access to Health and Disability Services for New Zealanders With Impaired Vision During the COVID-19 Pandemic 2020–2022. (November 2022) - Good, Gretchen A.; Nazari Orakani, Solmaz; Officer, Tara N.; Roguski, Michael; McBride-Henry, Karen
Introduction: The COVID-19 pandemic has affected access to health and social services globally, leading to delays in accessing appropriate care. However, while there is a growing base of research into service access for the general population, there remains scarce information on the implications of the pandemic on disabled people. This article describes issues with health and disability support access for people with impaired vision in Aotearoa New Zealand (Aotearoa).Methods: Applying an Interpretive Description methodology, 62 interviews were conducted with disabled people; 10 of these individuals identified as having impaired vision. Findings were analyzed thematically for the entire group of 62, representing varied impairment groups, and then for the 10 who had impaired vision.Results: Five key themes arose from the interviews, including transportation difficulties, mental distress, loss of community, loss of physical contact and signals, and general loss of support. Participants identified that this loss of support occurred at multiple levels, meaning that the disability and healthcare system as a whole was ill-equipped to manage their needs. Participants reported a lag-time in accessing care, meaning that the effects of the pandemic are still felt due to a lack of available support and resources.Discussion: This article remains one of a few studies to look at the implications of the pandemic on access to health and disability services for those with impaired vision. It highlights that despite Aotearoa's good track record in managing the pandemic, groups were forgotten and marginalized by the collective response to managing COVID-19.Implications for Practitioners: Blindness professionals must be aware of the possible disadvantages and impacts of pandemics and other disasters on people with impaired vision and their access to health and disability services. Policymakers must include disabled people at the decision-making table so that the diverse needs of these populations are managed.